Competence of The Parties in A Transfer Under the Transfer of Property Act, 1882 - Azad, S A K; Nayak, Srinibas (International Journal of Psychosocial Rehabilitation, 2025)
The paper discusses the various aspects of The Transfer of Property Act, 1882, including the competence of the transferor and the transferee. The paper talks about the essential conditions that need to be fulfilled for a transfer to be valid such as inter vivos transfer, registration, etcetera. Conditions as regards to the competence of the transferor and transferee also have to be fulfilled. Minors, aliens, people of unsound minds and insolvents cannot make valid transfers. The paper concludes with discussing the need of the Act as regards to transfers and the provisions regarding the competence of the parties to a transfer.